Outcome report on gendering climate policy in Africa - Freeman, Kathlee; Mulema, Annet A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Globally, women and men tend to have different climate change vulnerabilities and benefit differently from climate change adaptation and mitigation efforts. This is due to a range of factors including access to resources and knowledge, time restraints, and inclusion in decision-making processes. Since its launch in 2011, gender has served as a cross-cutting theme for the CGIAR Research Program on Climate Change, Agriculture and Food Security, due to the critical need to understand gender differentiations in order to meet development goals, including the sustainable increase of agriculture production, poverty alleviation, improved food security, and more equitable outcomes for men and women. Policy remains an important component of development, making gender-inclusive and gender-responsive policy an important element of CCAFS’, most notably through the Gender and Social Inclusion (GSI) Flagship. This report aims to better understand and highlight the role of CCAFS GSI in gendering climate policy in Africa. A analysis of CCAFS documents, interviews with stakeholders, and a review of policy-related successes influenced by CCAFS is included in this report as well as a discussion about next steps in ongoing policy work.